The Learning Multicultural Content Exposition Text Writing Using CIRC and TTW Models Based on Personality Types of X Graders - Shofiah, Shofiah; Zulaeha, Ida (Pascasarjana Universitas Negeri Semarang, 2018)
The purpose of this research is to explain the effectiveness of learning skills of expository writing of multicultural exposition with CIRC model and TTW model based on personality type of student class X as well as explaining the interaction of learning writing exposition text in multicultural expression with CIRC model and TTW model based on personality type of student class X. This research uses a quasi-experimental factorial design. In this design, there are two experimental groups namely cooperative integrated reading and composition class and think talk write experiment class. The results of the study are (1) the CIRC model was effectively used in teaching expository writing for introverted students, (2) the TTW model was effectively used in teaching expository texts for extroverted learners, and (3) The CIRC model is more effective than the TTW model. The average value of both is 88.73 > 84.64. It shows that between CIRC class and TTW class there is a significant difference.